Adolescents' Mental Health and Human Capital: The Role of Socioeconomic Rank - Michaela Paffenholz (Center for Economic Studies and ifo Institute (CESifo), 2023)
I provide evidence on the causal effects of a student's relative socioeconomic status during high school on their mental health and human capital development. Leveraging data from representative US high schools, I utilize between-cohort differences in the distributions of socioeconomic status within schools in a linear fixed effects model to identify a causal rank effect. I find that a higher rank during high school improves a student's depression scores, cognitive ability, self-esteem and popularity. The rank effects are persistent with long-lasting consequences for adult depression and college attainment. Additional analyses emphasize the role of inequality in exacerbating these rank effects.
Keywords: I14; I23; I24; 330; rank; mental health; higher education